2019
DOI: 10.4103/jfmpc.jfmpc_765_19
|View full text |Cite
|
Sign up to set email alerts
|

Oral mucosal changes in pemphigus vulgaris and its treatment: A case report

Abstract: Pemphigus Vulgaris is an autoimmune disease that causes severe blistering of the skin and mucous membrane which are fragile and breaks away leaving erosions that are extremely painful. Here we report a case of a patient suffering from pemphigus vulgaris with typical oral manifestations. We have reported the effect of treatment after two consecutive recalls at an interval of 1 week where the patient got 100% relief from her previous signs and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Thus, PV was considered another differential diagnosis. Few studies have reported similar findings of lip lesions among PV patients [ 22 25 ].…”
Section: Discussionmentioning
confidence: 84%
“…Thus, PV was considered another differential diagnosis. Few studies have reported similar findings of lip lesions among PV patients [ 22 25 ].…”
Section: Discussionmentioning
confidence: 84%
“…Guidelines set by the British Association of Dermatologists recommended treatment of Pemphigus Vulgaris in two phases: Induction phase to control the disease and maintenance phase for consolidation and treatment tapering. [1,7] Depending on the response, the dose is gradually decreased to the minimum therapeutic dose, taken once daily to minimize side effects. The cornerstone of therapeutic approach is systemic and/or local corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%